Peritoneopericardial Diaphragmatic Hernia in a Persian Cat - Becerra Takei, Dinah Dantas; de Sousa, Marilaine Carlos; Andrade de Moura, Amanda Nery; Pina de Carvalho, Vitor de Moraes; Néto Souza, Ana Caroline da Silva; Peixoto, Tiago da Cunha; Mauro, Caio Biasi; Leal, Paula Velozo (Acta Scientiae Veterinariae, 2021)
Background: Peritoneopericardial diaphragmatic hernia is a congenital defect characterized by an anomalous communication between the abdominal cavity and pericardial sac, which can lead to displacement of the abdominal viscera into the thoracic cavity. The occurrence in felines is higher among long-haired breeds, mainly the Persian breed, possibly based onan autosomal recessive inheritance. The diagnosis of PPDH is performed by means of chest radiography with or without contrast, in association with other imaging tests such as ultrasonography and echocardiography. Our objective in this study was to report the occurrence and macroscopic changes in a case of peritoneopericardial diaphragmatic hernia in a Persian feline. Case: A 9-year-old male Persian cat weighing 3.4 kg was referred to the HPET-Private Veterinary Clinic, Salvador, Bahia, with an history of weight loss and chronic intermittent vomiting during the preceding 6 months, with lateral decubitus and breathing difficulties. Ultrasonography revealed findings suggestive of an infiltrative process in the stomach and duodenum, enlarged gastric lymph nodes, and some nodular images indicating slight displacement of the liver. Chest radiography revealed a cardiac silhouette with markedly enlarged dimensions associated with a dorsal deviation of the terminal trachea, and echocardiography revealed a small amount of pericardial effusion. The patient showed initial clinical improvement after blood transfusion; however, after 2 days, he exhibited significant clinical worsening and was therefore euthanized with the owner's consent. Post mortem evaluation revealed partial herniation of the liver and gallbladder into the chest cavity through a diaphragmatic hernia ring. The heart was partially surrounded by the left medial lobe of the liver, which was displaced into the pericardial sac. Herniated hepatic lobes had an irregular capsular surface with evident lobulation and tension lipidosis. In the abdominal cavity, the remainder of the liver (right lateral and medial lobes) was observed to be slightly enlarged, with an irregular surface, diffusely reddish with intense evidence of the lobular pattern and white and firm multifocal areas (fibrosis). In the duodenum, close to the pylorus, there was a nodule measuring 2.8 x 2.5 x 1.0 cm, with a whitish and ulcerated surface. When cut, it was soft and exhibited a homogeneous, whitish compact surface.Histopathological examinationshowed marked proliferation of fibrous connective tissue, which for the most part separated the lobes by septa and surrounded the portal space (fibrosis), a marked diffuse chronic inflammatory infiltrate composed of lymphocytes and plasma cells. In addition, marked bile duct hyperplasia and multifocal areas of fatty degeneration (steatosis). Discussion: The diagnosis was based on the association of clinical and pathological findings. Considering the age and clinical signs presented by the patient in this report, as well as the presence of few radiographic signs that were indicative of PPDH, the first differential diagnosis thought was pericardial neoplasia. Peritoneopericardial diaphragmatic hernia in felines is always of congenital origin and may occur asymptomatically depending on the number and involvement of herniated viscera. In this case, the patient's diagnosis of peritoneopericardial hernia was a necropsy finding; the fact that in agreement with previous reports of high rates of incidental diagnoses reinforces the importance of performing necropsy for confirmation or diagnosis of unexpected pathologies. In the present case, peritoneopericardial diaphragmatic hernia in isolation may not have led to severe anemia that culminated in the patient's death. The anatomopathological findings were compatible with biliary cirrhosis and multifocal liver fibrosis, accompanied by the presence of anemia and consequent hypovolemia. Keywords: congenital diaphragmatic hernia, congenital abnormalities, cats. Título: Hérnia Diafragmática Peritoneopericárdica em um Felino da Raça Persa Descritores: hérnia diafragmática congênita, anomalias congênitas, felinos.